The Urgency of Developing Digital Teaching Modules with Luwu Cultural Context for Literacy Skills - Muhammad Rusli Baharuddin; Fitriani Fitriani; Andi Wafda (AL-ISHLAH: Jurnal Pendidikan, 2025)
The lack of local cultural representation in teaching materials and literacy challenges in the digital era highlight the need for innovative instructional resources. Developing digital teaching modules that enhance literacy while reinforcing cultural identity is crucial. This study aims to develop a Luwu Culture-Based Digital Teaching Module to improve students' literacy skills. This study employs a Research and Development (RD) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation phases. Data collection involves qualitative and quantitative methods to assess validity, practicality, and effectiveness. Findings indicate that the module is highly valid, with an average validity score of 81%, demonstrating strong relevance, comprehensiveness, and clarity. The module’s practicality is rated as excellent, with a mean score of 88%, indicating ease of use, learning effectiveness, and efficiency in implementation. The integration of local cultural elements into literacy instruction provides a meaningful learning experience, fostering students' engagement and comprehension of informational and literary texts. By embedding cultural narratives and traditions, the module enhances literacy skills while strengthening cultural identity. This study demonstrates that a Luwu Culture-Based Digital Teaching Module is a valid and practical tool for literacy development. Its adaptability to diverse cultural contexts suggests its potential for broader application in literacy education. Future research should explore its long-term impact on student learning outcomes.